Climate Change: A Study of Air Temperature Trend and Variation in the City of Bengkulu - Nita, Linda Tria; Prawito, Priyono; Sudjatmiko, Sigit; Anwar , Anang (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
Climate change is noticeable but the impact and the change are not easily detected. The most pronounced and easily detected climate change is air temperature changes, which affect both the state of natural ecosystems and human social life. Increasing climate and weather variability and extreme climate events affect human life and natural systems more detrimental than the effect of climate change in the form of climate means. This study aims to determine the change in air temperature and the presence of extreme air temperature during the last 37 years. Data of average air temperature (AAT), maximum air temperature (MAT), and minimum air temperature (MiAT) from 1985 to 2022 from the P. Baai Station and Fatmawati Station were used. Trendline analysis were performed to find an increasing trend of air temperature, while the frequency distribution analysis was performed to find extreme climate even. The study concluded that AAT in the City of Bengkulu increase about 0.026oC yr-1 , the MAT increase about 0.005oC yr-1, and the MiAT increase 0.025oC yr-1 during the last 37 years. The extreme climate event however, neither low nor high air temperature was detected. The AAT, MAT and MiAT at present are 26.4oC, 31.3oC, and 21.3oC, respectively.